Underground telephone cables - Clark, Roy H. (My University, 1907)
Introduction: For many years after the introduction of the telephone the difficulties of working through underground wires seemed almost insurmountable. The electrostatic capacity of the underground wires of early days was so much greater than that of overhead circuits as to materially interfere with telephonic transmission. In late years however, the methods of insulation have been so much improved that the underground construction of telephone circuits is the general rule in large cities, and is rapidly being adopted even in small towns. The standard type of cable for telephone work contains two hundred pairs of insulated wires. One hundred pairs and fifty pairs and various smaller numbers are used for distribution. The insulation of cables is now mostly of dry paper. The requisite number of pairs of wires to form the desired cable is taken, and each wire insulated from its mate by a loose wrapping of well dried paper. It is usual to color in some manner the individual wires after they are wrapped, in order that the component of each pair may be known without testing. The wires to be wrapped are simply separated by a sheet of paper, and then lightly twisted together, the twist being sufficient to hold both conductors and insulation in their proper relative positions. A single twisted pair of wires is taken to form the core of the completed cable and around that the required number of pairs are assembled in regular layers, each successive layer being wound about the preceding one with a reverse twist, making a complete turn in from eighteen to thirty-six inches. The use of paper gives an insulator of low electrostatic capacity yet strong enough to maintain an insulation of many thousand meg ohms against the weak electro-motive force of telephone currents. By twisting the several pairs of wires very loosely about each other a considerable volume filled with air remains. Capacity is decreased by leaving as much space between conductors as possible.
Citation: Clark, Roy H. Underground telephone cables. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Telephone Cables; Underground Cables; Insulating Wires; Electrostatics; Theses